(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the settlement of some representatives of the genus urbophilus rodentia on cultural landscapes in the territory of the Guzar district of Kashkadarya region. The factors contributing to ecology, urbanization and urbanization of representatives of this genus, mechanisms and consequences of their impact are identified. The development of adaptive reactions in urbanophilic species, ensuring their adaptation to the cultural landscape, and changes occurring in the ethology of species as a result of adaptation, and its significance are revealed. The cultural landscapes of the plain zone of the southern territory of Uzbekistan are characterized as peculiar habitats that preserve the biodiversity of the animal world.